Relationship between helium isotopes and focal depths of low-frequency earthquake, Northeastern Japan - Yukino Yamazaki; Arisa Narita; Koji Umeda; Hirochika Sumino; Takuto Maeda; Tadashi Amano (Geoscience Letters)
Abstract Low-frequency earthquakes (LFEs) observed around volcanoes are often interpreted as reflecting the boundary of the magma transport channels or magma reservoirs. On the other hand, the occurrence of mantle-derived helium is closely related to current or recent magmatism in subduction zones, owing to mantle melting being the primary mechanism for the transfer of primordial 3He from the mantle to the lithosphere. The elevated 3He/4He ratios observed surrounding volcanoes could indicate the presence of a magmatic plumbing system. Therefore, it is meaningful to investigate the relationship between the helium isotope variations and the location of LFEs in volcanic regions. There appears to be good correlation between helium isotope ratios and focal depths of LFEs observed in 31 volcanic regions of Northeast Japan. The helium isotope ratio increases as the focal depth of the low-frequency earthquake decreases. These findings indicate that the shallower the depth of the magma reservoir, the smaller the contamination of primordial helium with crustal radiogenic helium, resulting in higher helium isotopes observed at the surface. Many volcanic hazard factors, such as the probability and duration of an eruption, the eruption style, and the probability of triggering large landslides or caldera collapses, are related to the depth of the magma source. Combining helium isotope monitoring with low-frequency earthquake observations has the potential to improve the reliability of future eruption prediction.